2014
DOI: 10.1007/s00726-014-1708-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine and potential interactions with caffeine on cardiovascular function

Abstract: The major impetus behind the rise in energy drink popularity among adults is their ability to heighten mental alertness, improve physical performance and supply energy. However, accompanying the exponential growth in energy drink usage have been recent case reports and analyses from the National Poison Data System, raising questions regarding the safety of energy drinks. Most of the safety concerns have centered on the effect of energy drinks on cardiovascular and central nervous system function. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 114 publications
1
42
0
1
Order By: Relevance
“…); thus leading to the European Union's Scientific Committee on Food to summarize that, in relation to the cardiovascular effects of energy drinks, “if there are any interactions between caffeine and taurine, taurine might reduce the cardiovascular effects of caffeine” (Scientific Committee on Food; European Commission ) (for a recent review of evidence, see Schaffer et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…); thus leading to the European Union's Scientific Committee on Food to summarize that, in relation to the cardiovascular effects of energy drinks, “if there are any interactions between caffeine and taurine, taurine might reduce the cardiovascular effects of caffeine” (Scientific Committee on Food; European Commission ) (for a recent review of evidence, see Schaffer et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study was not designed to test this hypothesis, our findings showing very similar hemodynamic pathways being influenced by sfRB and W + caff, suggest it is unlikely that taurine was responsible for, or enhanced, the pressor effect of RB. On the contrary, taurine has been shown to decrease both systolic and diastolic blood pressure (Fujita et al 1987), and, at a population level, dietary taurine is associated with decreased risk of CVD (Yamori et al 2010); thus leading to the European Union's Scientific Committee on Food to summarize that, in relation to the cardiovascular effects of energy drinks, "if there are any interactions between caffeine and taurine, taurine might reduce the cardiovascular effects of caffeine" (Scientific Committee on Food; European Commission 2003) (for a recent review of evidence, see Schaffer et al 2014). While a sugar-only test was not included in the present study, recent work in this laboratory (Grasser et al 2014a) has shown no change in BP following ingestion of 60 g of sucrose (1.59 the sugar content contained within the volume of RB investigated here), thereby suggesting that the acute BP-elevating effect of RB is likely to be due to an interaction between sugar and caffeine on the hemodynamic system rather than sugar per se.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors proposed to athletes a diet supplement of 2-4 g of taurine to fight against sleep-inducing effect of intense eccentric contractions [148][149][150]. In opposition to previous authors, other scientists did not confirm any potential positive effects of ß-alanine in healthy athletes [151][152][153][154].…”
Section: A) Classical Protein Feedingmentioning
confidence: 88%
“…Taurine, l ‐carnitine, and panax ginseng are some additives found in energy drinks and have conflicting physiologic effects. The preponderance of evidence suggests taurine is more likely an antiarrhythmic than a proarrhythmic . A correlation between l ‐carnitine deficiency and short QT syndrome has been postulated .…”
Section: Discussionmentioning
confidence: 99%